Exploring the Relationship Between Social Commerce Features and Consumers’ Repurchase Intentions: The Mediating Role of Perceived Value - Guo, Jinyuan; Li, Lei (Frontiers in Psychology, 2022)
The popularity of social media, such as WeChat and Weibo in China, has provided an opportunity to develop social commerce. Although shopping through social commerce platforms is widely favored by consumers, the factors affecting consumers’ decision-making behavior in the social commerce environment remain unclear. Therefore, from the perspective of the stimulus–organism–response (SOR) theory, we construct a consumer repurchase decision model in the social commerce environment and analyze the influencing mechanism of social commerce features (interactivity, recommendations, and feedback) on perceived value (utilitarian value and hedonic value) and consumers’ repurchase intention. The empirical results found that social commerce features are positively related to the generation of perceived value, which in turn drives consumers to form repurchase intentions. We also found some mediating effects of perceived value. The study’s conclusions clarify the intrinsic influence mechanism of social commerce features on consumers’ perceived value and repurchase intentions. In addition, it can provide some theoretical guidance for future research and business.